Porous zinc negative electrode, preparation method thereof and battery

By etching the zinc plate in the acid solution to form a nanosheet-like structure, and modifying the porous structure in the mixed solution of tin salt and acid, the existing zinc negative electrode has been solved, and more efficient zinc negative electrode performance has been achieved.

CN119673938APending Publication Date: 2025-03-21CHAOWEI POWER GROUP CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411642561.1
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-18
Publication Date
2025-03-21

AI Technical Summary

Technical Problem

The existing zinc negative electrode is a block-like structure with a small specific surface area and poor corrosion resistance, resulting in large potential polarization of zinc ion batteries during deposition/stripping, low Coulomb efficiency and poor cycle stability.

Method used

By acid etching the zinc plate in the acid solution, chemically unstable components are removed to form a nanosheet-like structure, and then react in a mixed solution containing tin salt and acid to form a porous structure, increasing the specific surface area and zinc nucleation sites, and improving corrosion resistance.

Benefits of technology

It has achieved the reduction of the polarization potential of the zinc negative electrode, improved its corrosion resistance and cycle stability, and the preparation method is simple, low cost and wide application range.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119673938A_ABST
    Figure CN119673938A_ABST
Patent Text Reader

Abstract

The invention discloses a porous zinc negative electrode, a preparation method thereof and a battery, and belongs to the technical field of zinc-based batteries. The problems that an existing zinc negative electrode is of a blocky structure and is small in specific surface area and poor in corrosion resistance, and a battery prepared from the existing zinc negative electrode is high in polarization potential and poor in cycling stability are solved. The preparation method of the porous zinc negative electrode comprises the following steps: carrying out acid etching on a zinc plate in acid A; and putting the etched zinc plate into a mixed solution containing tin salt and acid B for reaction to obtain the porous zinc negative electrode. The porous zinc negative electrode prepared by the preparation method disclosed by the invention is good in corrosion resistance.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of zinc-based batteries, and in particular to a porous zinc negative electrode and a preparation method thereof, and a battery. Background Art

[0002] Aqueous zinc-ion batteries have the advantages of low cost, high theoretical capacity, intrinsic safety and environmental friendliness, showing great application prospects in the field of large-scale energy storage. However, the zinc negative electrode faces serious problems such as hydrogen evolution reaction, corrosion, passivation and dendrite growth, resulting in large potential polarization, low coulombic efficiency and poor cycle stability during the deposition / stripping process. This greatly affects the electrochemical performance of zinc-ion batteries and limits their further application. Summary of the invention

[0003] In view of the above analysis, the present invention aims to provide a porous zinc negative electrode and a preparation method and a battery, so as to solve one of the following technical problems: the existing zinc negative electrode is a block structure with a small specific surface area and poor corrosion resistance. The battery prepared using the existing zinc negative electrode faces the technical problems of high polarization potential and poor cycle stability.

[0004] The purpose of the present invention is mainly achieved through the following technical solutions:

[0005] The present invention provides a method for preparing a porous zinc negative electrode, comprising:

[0006] Step 1, etching the zinc plate in acid A;

[0007] Step 2: placing the etched zinc plate into a mixed solution containing tin salt and acid B for reaction to obtain a porous zinc negative electrode.

[0008] Furthermore, in step 1, acid A is one or more of hydrochloric acid, sulfuric acid, phosphoric acid, oxalic acid, nitric acid, tartaric acid, acetic acid and boric acid.

[0009] Furthermore, in step 1, the concentration of acid A is 0.1 to 12 mol / L.

[0010] Furthermore, in step 2, the tin salt is a soluble tin salt.

[0011] Furthermore, the soluble tin salt is one or more of sodium stannate, potassium stannate, tin dichloride, tin tetrachloride and stannous sulfate.

[0012] Furthermore, in step 2, the concentration of the tin salt in the mixed solution is 5 to 50 mmol / L.

[0013] Furthermore, in step 2, acid B is one or more of citric acid, hydrochloric acid, sulfuric acid and phosphoric acid.

[0014] Furthermore, in step 2, the reaction temperature is 25-60°C.

[0015] The present invention also provides a porous zinc negative electrode, which is prepared by the above-mentioned preparation method.

[0016] The present invention also provides a battery, which comprises the porous zinc negative electrode.

[0017] Compared with the prior art, the present invention can achieve at least one of the following beneficial effects:

[0018] (1) In the preparation method of the porous zinc negative electrode of the present invention, an acid solution is used to etch the zinc plate to remove chemically unstable components and simultaneously prepare a zinc negative electrode with a nanosheet structure, so as to reduce the polarization potential of the zinc negative electrode; subsequently, a porous structure is formed by tin metal modification, thereby increasing the specific surface area and zinc nucleation sites of the zinc negative electrode and improving the corrosion resistance of the zinc negative electrode.

[0019] (2) The preparation method of the porous zinc negative electrode of the present invention is simple, low-cost, can be mass-produced, and has a wide range of applications.

[0020] (3) The porous structure of the porous zinc negative electrode of the present invention is not only conducive to the uniform distribution of the electric field / current and ion field on the negative electrode surface, but also can alleviate the volume change of the negative electrode during the cycle and reduce the internal stress of zinc deposition; the metal tin modification on the surface of the nanosheet array structure can promote the uniform deposition of zinc and alleviate the corrosion of the zinc negative electrode, thereby improving the corrosion resistance of the zinc negative electrode. The corrosion current of the porous zinc negative electrode of the present invention is 0.0227mA cm -2 Below, for example 0.0028~0.0227mA cm -2 .

[0021] (4) The battery of the present invention includes a porous zinc negative electrode, and the battery has good cycle stability. For example, the assembled symmetrical battery exhibits low polarization potential and excellent cycle stability. The polarization potential of the symmetrical battery of the present invention is below -40 to +42 mV.

[0022] In the present invention, the above-mentioned technical solutions can also be combined with each other to achieve more preferred combination solutions. Other features and advantages of the present invention will be described in the subsequent description, and some advantages can become obvious from the description, or can be understood by practicing the present invention. The purpose and other advantages of the present invention can be realized and obtained through the contents particularly pointed out in the embodiments of the description and the drawings. BRIEF DESCRIPTION OF THE DRAWINGS

[0023] The drawings are only for the purpose of illustrating particular embodiments and are not to be considered limiting of the present invention. Like reference symbols denote like components throughout the drawings.

[0024] Figure 1 is a scanning electron microscope image of the porous zinc negative electrode of Example 1;

[0025] Figure 2 XRD diagrams of samples of Example 1, Comparative Example 1 and Comparative Example 2;

[0026] Figure 3 1 is a cycle performance diagram of the symmetrical battery of Example 1;

[0027] Figure 4 is a scanning electron microscope image of the porous zinc negative electrode of Example 2;

[0028] Figure 5 is a cycle performance diagram of the symmetrical battery of Example 2;

[0029] Figure 6 This is a scanning electron microscope image of the porous zinc negative electrode of Example 3;

[0030] Figure 7 is a cycle performance diagram of the symmetrical battery of Example 3;

[0031] Figure 8 is a scanning electron microscope image of the porous zinc negative electrode of Example 4;

[0032] Fig. 9 is a scanning electron microscope image of the porous zinc negative electrode of Example 5;

[0033] Fig.10 is a scanning electron microscope image of the porous zinc negative electrode of Example 6;

[0034] Fig.11 This is a scanning electron microscope image of the zinc negative electrode of Comparative Example 1;

[0035] Fig.12 1 is a cycle performance diagram of the symmetrical battery of Comparative Example 1;

[0036] Fig.13 This is a scanning electron microscope image of the zinc negative electrode of Comparative Example 2;

[0037] Fig.14 This is a scanning electron microscope image of the zinc negative electrode of Comparative Example 3. DETAILED DESCRIPTION

[0038] The preferred embodiments of the present invention will be described in detail below in conjunction with the accompanying drawings, wherein the accompanying drawings constitute a part of the present invention and are used together with the embodiments of the present invention to illustrate the principles of the present invention, but are not used to limit the scope of the present invention.

[0039] The present invention provides a method for preparing a porous zinc negative electrode, comprising:

[0040] Step 1, etching the zinc plate in acid A;

[0041] Step 2: placing the etched zinc plate into a mixed solution containing tin salt and acid B for reaction to obtain a porous zinc negative electrode.

[0042] Specifically, in the above step 1, the acid A can be one or more of hydrochloric acid, sulfuric acid, phosphoric acid, oxalic acid, nitric acid, tartaric acid, acetic acid and boric acid.

[0043] Specifically, in the above step 1, if the concentration of the acid is too high, the zinc plate will be over-corroded, and the nano-sheet structure cannot be selectively retained. In addition, the thickness of the zinc plate will be significantly reduced or even leave holes; if the concentration of the acid is too low, it is difficult to form a nano-sheet structure on the surface of the zinc plate. Therefore, the concentration of acid A is controlled to be 0.1-12 mol / L, such as 0.5 mol / L, 1 mol / L, 2 mol / L, 3 mol / L, 4 mol / L, 5 mol / L, 6 mol / L, 7 mol / L, 8 mol / L, 9 mol / L, 10 mol / L, 11 mol / L.

[0044] Specifically, the specific steps of the above step 1 include: placing the zinc plate in the solution of acid A, ultrasonic reaction, washing with water to neutrality after the reaction, and drying. If the ultrasonic time is too short, the acid etching effect is not obvious; if the ultrasonic time is too long, the zinc plate will be excessively corroded or even completely dissolved in the acid solution, and the formed nano-sheet structure may be destroyed. Therefore, the ultrasonic reaction is controlled to be 1 to 30 minutes.

[0045] Specifically, in order to reduce impurity contamination, deionized water can be used.

[0046] Specifically, in the above step 1, the zinc plate is etched by an acid solution to remove chemically unstable components, thereby obtaining a zinc plate with a nano-sheet structure.

[0047] Specifically, in the above step 2, the tin salt is a soluble tin salt.

[0048] Specifically, in the above step 2, the tin salt may be one or more of sodium stannate, potassium stannate, tin dichloride, tin tetrachloride and stannous sulfate.

[0049] Specifically, in the above step 2, if the concentration of the tin salt is too high, the formed tin metal layer is too thick, which reduces the porosity of the negative electrode surface; if it is too low, the tin metal loading is small, and it is difficult to completely wrap the zinc plate surface, so the corrosion inhibition effect is not significant. Therefore, the concentration of the tin salt in the mixed solution is controlled to be 5 to 50 mmol / L, such as 10 mmol / L, 20 mmol / L, 30 mmol / L, and 40 mmol / L.

[0050] Specifically, in the above step 2, the acid B can be one or more of citric acid, hydrochloric acid, sulfuric acid and phosphoric acid.

[0051] Specifically, in the above step 2, if the concentration of the acid is too high, the zinc plate will be corroded during the preparation process, thereby affecting the structure and performance of the porous negative electrode; if the concentration is too low, it is difficult to form a uniform metal tin layer on the surface of the zinc plate in situ. Therefore, the concentration of acid B is controlled to be 0.01-0.5 mol / L, such as 0.05 mol / L, 0.1 mol / L, 0.2 mol / L, 0.3 mol / L, 0.4 mol / L.

[0052] Specifically, in the above step 2, if the reaction temperature is too high, the reaction will be violent, resulting in an uneven Sn metal layer; if the reaction temperature is too low, the reaction rate will be slow; if the reaction time is too low, the Sn metal loading will be small and uneven; if the reaction time is too long, the Sn metal layer will be too thick, thus affecting the polarization potential of the battery. Therefore, the reaction temperature is controlled to be 25 to 60°C, such as 30°C, 35°C, 40°C, 45°C, 50°C, 55°C; the reaction time is 2 to 20 minutes, such as 3 minutes, 4 minutes, 5 minutes, 6 minutes, 8 minutes, 10 minutes, 13 minutes, 15 minutes, 16 minutes, 18 minutes.

[0053] Preferably, in the above step 2, acid B is citric acid, the solution of which is weakly acidic, which can not only promote the conversion of stannate into Sn 2+ , making Sn 2+ It replaces Zn to form a metal Sn layer on the surface of the zinc negative electrode, and it is not easy to destroy the nanosheet layer structure; in addition, the citrate ion has a complexing effect, which can effectively control the reaction rate to obtain a uniformly modified porous Sn metal layer on the zinc plate.

[0054] Specifically, before the above step 1, the process also includes: cutting the zinc plate into a certain size, washing to remove surface impurities, drying, and flattening the zinc plate after drying.

[0055] Specifically, in the above step 2, after the reaction is completed, the mixture is washed with deionized water until it becomes neutral and dried. The drying temperature is controlled to be 50-60°C.

[0056] The present invention also provides a porous zinc negative electrode, which is prepared by the above preparation method.

[0057] Specifically, the surface of the zinc plate of the porous zinc negative electrode of the present invention is a porous structure, including a nano-sheet structure and loaded tin metal.

[0058] Specifically, the surface of the zinc plate of the porous zinc negative electrode of the present invention has a nano-sheet structure, and the surface of the nano-sheet structure is loaded with tin metal.

[0059] Specifically, the porosity of the porous zinc negative electrode is greater than 22%, for example, 22.9% to 80%.

[0060] Specifically, the above-mentioned pores include micrometer-scale secondary pores.

[0061] Specifically, the above-mentioned pores also include nanoscale primary pores.

[0062] Specifically, the aperture of the primary pores is in the range of 50 to 900 nanometers, and the aperture of the secondary pores is in the range of 1 to 6 micrometers.

[0063] The present invention also provides a battery, which comprises the porous zinc negative electrode.

[0064] In the preparation method of the porous zinc negative electrode of the present invention, an acid solution is used to etch the zinc plate to remove chemically unstable components and simultaneously prepare a zinc negative electrode with a nanosheet structure to reduce the polarization potential of the zinc negative electrode; subsequently, a porous structure is formed by tin metal modification to increase the specific surface area and zinc nucleation sites of the zinc negative electrode, while improving the corrosion resistance of the zinc negative electrode.

[0065] The preparation method of the porous zinc negative electrode of the present invention is simple, low in cost, can be mass-produced, and has a wide range of applications.

[0066] The porous structure of the porous zinc negative electrode of the present invention is not only conducive to the uniform distribution of the electric field / current and ion field on the negative electrode surface, but also can alleviate the volume change of the negative electrode during the cycle and reduce the internal stress of zinc deposition; the metal tin modification on the surface of the nanosheet array structure can promote the uniform deposition of zinc and alleviate the corrosion of the zinc negative electrode, thereby improving the corrosion resistance of the zinc negative electrode. The corrosion current of the porous zinc negative electrode of the present invention is 0.0227mA cm -2 Below, for example 0.0028~0.0227mAcm -2 .

[0067] The battery of the present invention comprises a porous zinc negative electrode, and the battery has good cycle stability. For example, the assembled symmetrical battery exhibits low polarization potential and excellent cycle stability (more than 540 hours).

[0068] The technical solution of the present invention is further explained below in conjunction with specific examples. It should be noted that the data in the examples are all exemplary descriptions, and the dosage can be determined according to actual needs during the production process.

[0069] Example 1

[0070] This embodiment provides a porous zinc negative electrode and a preparation method thereof, and a battery. The preparation method of the porous zinc negative electrode includes:

[0071] (1) Cut the zinc plate into 3 cm × 4 cm pieces, wash with ethanol and water to remove organic matter on the surface of the zinc plate, dry it, and then use a press to flatten the cut zinc plate;

[0072] (2) preparing a hydrochloric acid solution with a hydrochloric acid concentration of 2 mol / L, adding the washed and dried zinc plate, and subjecting to ultrasonic reaction for 5 min. After the reaction, the zinc plate was washed with deionized water until it was neutral, and then dried at 60° C.;

[0073] (3) The zinc plate obtained in step (2) was immersed in a mixed solution containing 20 mmol / L sodium stannate and 0.2 mol / L citric acid, and reacted at 40° C. for 5 min. After the reaction, it was washed with deionized water until neutral, and finally dried at 60° C. to obtain a porous zinc negative electrode.

[0074] This embodiment also provides a symmetrical battery assembled using the porous zinc negative electrode of embodiment 1. Symmetrical battery assembly and electrochemical performance test conditions: The porous zinc negative electrode of embodiment 1 is used as the working electrode (the working electrode area is 24 cm 2 ), two zinc plates treated in step (1) were placed on both sides of the diaphragm as counter electrodes to assemble a Zn / / Zn symmetrical cell. The symmetrical cell was first charged at 0.5 mA cm -2 , with a surface capacity of 2.5 mAh cm -2 5 cycles under the condition of activation, and then at a current density of 1 mA cm -2 , with a surface capacity of 5 mAh cm -2 The electrochemical performance tests were carried out under the conditions of .

[0075] Figure 1 This is a scanning electron microscope image of the porous zinc negative electrode prepared in Example 1. The porosity of the porous zinc negative electrode in Example 1 is 70.9%. The surface of the porous zinc negative electrode is distributed with nanometer-scale primary pores and micrometer-scale secondary pores, wherein the pore size of the primary pores ranges from 50 to 900 nanometers, and the pore size of the secondary pores ranges from 1 to 3 micrometers.

[0076] The XRD pattern of the porous zinc negative electrode of Example 1 is as follows Figure 2 As shown. The characteristic peaks of the porous zinc negative electrode of Example 1 at 30.6° and 32° are attributed to the (200) and (101) crystal planes of metallic tin, which shows that metallic tin is successfully modified on the surface of the nanosheet array structure. Metallic tin has zinc affinity and good corrosion resistance, which can promote uniform deposition of zinc while alleviating corrosion of the zinc negative electrode.

[0077] Table 1 shows the corrosion current of the porous zinc negative electrode. It can be seen that the corrosion current of the porous zinc negative electrode of this embodiment is low, which is 0.0028 mA cm -2 .

[0078] like Figure 3 The graph shows the cycle performance of the symmetrical battery. It can be seen that the symmetrical battery of this embodiment exhibits a low polarization potential (-20 to +24 mV) and a cycle stability of more than 900 h.

[0079] Example 2

[0080] This embodiment provides a porous zinc negative electrode and a preparation method thereof, and a battery. The preparation method of the porous zinc negative electrode includes:

[0081] (1) Cut the zinc plate into 3 cm × 4 cm pieces, wash with ethanol and water to remove organic matter on the surface of the zinc plate, dry it, and then use a press to flatten the cut zinc plate;

[0082] (2) preparing a hydrochloric acid solution with a hydrochloric acid concentration of 1 mol / L, adding the washed and dried zinc plate, and subjecting to ultrasonic reaction for 10 min. After the reaction, the zinc plate was washed with deionized water until it was neutral, and then dried at 60° C.;

[0083] (3) The zinc plate obtained in step (2) was immersed in a mixed solution containing 30 mmol / L sodium stannate and 0.5 mol / L citric acid, and reacted at 40° C. for 15 min. After the reaction, it was washed with deionized water until neutral, and finally dried at 60° C. to obtain a porous zinc negative electrode.

[0084] This embodiment also provides a symmetrical battery assembled using the porous zinc negative electrode of embodiment 2. The symmetrical battery assembly and electrochemical performance test conditions are basically the same as those of embodiment 1, and will not be repeated here.

[0085] Figure 4 This is a scanning electron microscope image of the porous zinc negative electrode prepared in Example 2. The porosity of the porous zinc negative electrode in Example 2 is 22.9%. The surface of the porous zinc negative electrode contains nanoscale primary pores and micrometer-scale secondary pores, wherein the pore size of the primary pores ranges from 100 to 600 nanometers, and the pore size of the secondary pores ranges from 1 to 6 micrometers.

[0086] The corrosion current of the porous zinc negative electrode of this embodiment is shown in Table 1. It can be seen that the corrosion current of the porous zinc negative electrode of this embodiment is low, which is 0.0024 mA cm -2 .

[0087] Figure 5 : is the cycle performance diagram of the symmetrical battery of Example 2. It can be seen that the symmetrical battery of this example exhibits a low polarization potential (-32 to +39 mV) and a cycle stability of more than 850 h.

[0088] Example 3

[0089] This embodiment provides a porous zinc negative electrode and a preparation method thereof, and a battery. The preparation method of the porous zinc negative electrode includes:

[0090] (1) Cut the zinc plate into 3 cm × 4 cm pieces, wash with ethanol and water to remove organic matter on the surface of the zinc plate, dry it, and then use a press to flatten the cut zinc plate;

[0091] (2) preparing a solution with a hydrochloric acid concentration of 2 mol / L, adding the washed and dried zinc plate, and subjecting the zinc plate to ultrasonic reaction for 5 min. After the reaction, washing the zinc plate with deionized water until it is neutral, and drying the zinc plate at 60° C.

[0092] (3) The zinc plate obtained in step (2) was immersed in a mixed solution containing 20 mmol / L sodium stannate and 0.2 mol / L citric acid, and reacted at 40° C. for 2 min. After the reaction, it was washed with deionized water until neutral, and finally dried at 60° C. to obtain a porous zinc negative electrode.

[0093] This embodiment also provides a symmetrical battery assembled using the porous zinc negative electrode of embodiment 3. The symmetrical battery assembly and electrochemical performance test conditions are basically the same as those of embodiment 1, and will not be repeated here.

[0094] Figure 6 This is a scanning electron microscope image of the porous zinc negative electrode prepared in Example 3. The porosity of the porous zinc negative electrode in Example 3 is 78.6%. Micron-sized secondary pores are distributed on the surface of the porous zinc negative electrode.

[0095] The corrosion current of the porous zinc negative electrode of this embodiment is shown in Table 1. It can be seen that the corrosion current of the porous zinc negative electrode of this embodiment is low, which is 0.0158 mA cm -2 .

[0096] Figure 7 The figure is a cycle performance diagram of the symmetrical battery of Example 3. It can be seen that the symmetrical battery of this example exhibits a low polarization potential (-40 to +40 mV) and a cycle stability of more than 850 h.

[0097] Example 4

[0098] This embodiment provides a porous zinc negative electrode and a preparation method thereof, and a battery. The preparation method of the porous zinc negative electrode includes:

[0099] (1) Cut the zinc plate into 3 cm × 4 cm pieces, wash with ethanol and water to remove organic matter on the surface of the zinc plate, dry it, and then use a press to flatten the cut zinc plate;

[0100] (2) preparing a 2 mol / L hydrochloric acid solution, adding the washed and dried zinc plate, and subjecting to ultrasonic reaction for 5 min. After the reaction, washing with deionized water until neutral, and drying at 60° C.

[0101] (3) The zinc plate obtained in step (2) was immersed in a mixed solution containing 20 mmol / L sodium stannate and 0.2 mol / L HCl, and reacted at 40° C. for 5 min. After the reaction, it was washed with deionized water until neutral, and finally dried at 60° C. to obtain a porous zinc negative electrode.

[0102] This embodiment also provides a symmetrical battery assembled using the porous zinc negative electrode of embodiment 4. The symmetrical battery assembly and electrochemical performance test conditions are basically the same as those of embodiment 1, and will not be repeated here.

[0103] Figure 8 This is a scanning electron microscope image of the porous zinc negative electrode prepared in Example 4. The porosity of the porous zinc negative electrode in Example 4 is 44.48%. The surface of the porous zinc negative electrode is distributed with nanometer-scale primary pores and micrometer-scale secondary pores, wherein the pore size of the primary pores ranges from 200 to 900 nanometers, and the pore size of the secondary pores ranges from 1 to 5 micrometers. Figure 8 It can be seen that due to the lack of chelation effect of HCl, the surface morphology of the porous zinc negative electrode prepared in Example 4 is uneven, and the surface morphology of the zinc negative electrode in different regions is inconsistent.

[0104] The corrosion current of the porous zinc negative electrode of this embodiment is shown in Table 1. It can be seen that the corrosion current of the porous zinc negative electrode of this embodiment is low, which is 0.0216 mA cm -2 .

[0105] The symmetrical battery of this example also exhibits low polarization potential (-38 to +42 mV) and excellent cycle stability (about 600 h).

[0106] Example 5

[0107] This embodiment provides a porous zinc negative electrode and a preparation method thereof, and a battery. The preparation method of the porous zinc negative electrode includes:

[0108] (1) Cut the zinc plate into 3 cm × 4 cm pieces, wash with ethanol and water to remove organic matter on the surface of the zinc plate, dry it, and then use a press to flatten the cut zinc plate;

[0109] (2) preparing a 2 mol / L hydrochloric acid solution, adding the washed and dried zinc plate, and subjecting to ultrasonic reaction for 5 min. After the reaction, washing with deionized water until neutral, and drying at 60° C.

[0110] (3) The zinc plate obtained in step (2) was immersed in a mixed aqueous solution containing 20 mmol / L sodium stannate and 0.2 mol / L citric acid, and reacted at 25° C. for 5 min. After the reaction, it was washed with deionized water until neutral, and finally dried at 60° C. to obtain a porous zinc negative electrode.

[0111] This embodiment also provides a symmetrical battery assembled using the porous zinc negative electrode of embodiment 5. The symmetrical battery assembly and electrochemical performance test conditions are basically the same as those of embodiment 1, and will not be repeated here.

[0112] Fig. 9This is a scanning electron microscope image of the porous zinc negative electrode prepared in Example 5. The porosity of the porous zinc negative electrode in Example 5 is 62.4%, and micrometer-sized secondary pores are distributed on its surface.

[0113] The corrosion current of the porous zinc negative electrode of this embodiment is shown in Table 1. It can be seen that the corrosion current of the porous zinc negative electrode of this embodiment is low, which is 0.0194 mA cm -2 .

[0114] The symmetrical battery of this example also exhibits low polarization potential (-35 to +40 mV) and excellent cycle stability (about 540 h).

[0115] Example 6

[0116] This embodiment provides a porous zinc negative electrode and a preparation method thereof, and a battery. The preparation method of the porous zinc negative electrode includes:

[0117] (1) Cut the zinc plate into 3 cm × 4 cm pieces, wash with ethanol and water to remove organic matter on the surface of the zinc plate, dry it, and then use a press to flatten the cut zinc plate;

[0118] (2) preparing a 2 mol / L hydrochloric acid solution, adding the washed and dried zinc plate, and subjecting to ultrasonic reaction for 5 min. After the reaction, washing with deionized water until neutral, and drying at 60° C.

[0119] (3) The zinc plate obtained in step (2) was immersed in a mixed aqueous solution containing 20 mmol / L sodium stannate and 0.2 mol / L citric acid, and reacted at 60° C. for 5 min. After the reaction, it was washed with deionized water until neutral, and finally dried at 60° C. to obtain a porous zinc negative electrode.

[0120] This embodiment also provides a symmetrical battery assembled using the porous zinc negative electrode of embodiment 6. The symmetrical battery assembly and electrochemical performance test conditions are basically the same as those of embodiment 1, and will not be repeated here.

[0121] Fig.10 This is a scanning electron microscope image of the porous zinc negative electrode prepared in Example 6. The porosity of the porous zinc negative electrode in Example 6 is 61.76%, and nanoscale primary pores and micron-scale secondary pores are distributed on its surface, wherein the pore size of the primary pores ranges from 100 to 850 nanometers, and the pore size of the secondary pores ranges from 1 to 3 micrometers.

[0122] The corrosion current of the porous zinc negative electrode of this embodiment is shown in Table 1. It can be seen that the corrosion current of the porous zinc negative electrode of this embodiment is low, which is 0.0227 mA cm -2 .

[0123] The symmetrical battery of this example also exhibits low polarization potential (-33 to +37 mV) and excellent cycle stability (about 700 h).

[0124] Example 7

[0125] This embodiment provides a porous zinc negative electrode and a preparation method thereof, and a battery. The preparation method of the porous zinc negative electrode includes:

[0126] (1) Cut the zinc plate into 3 cm × 4 cm pieces, wash with ethanol and water to remove organic matter on the surface of the zinc plate, dry it, and then use a press to flatten the cut zinc plate;

[0127] (2) preparing a mixed solution of hydrochloric acid and sulfuric acid with a concentration of 2 mol / L, adding the washed and dried zinc plate, and subjecting the zinc plate to ultrasonic reaction for 5 min. After the reaction, washing the zinc plate with deionized water until it is neutral, and drying the zinc plate at 60° C.

[0128] (3) The zinc plate obtained in step (2) was immersed in a mixed solution containing 20 mmol / L sodium stannate and 0.2 mol / L citric acid, and reacted at 40° C. for 5 min. After the reaction, it was washed with deionized water until neutral, and finally dried at 60° C. to obtain a porous zinc negative electrode.

[0129] The corrosion current of the porous zinc negative electrode of this embodiment is shown in Table 1. It can be seen that the corrosion current of the porous zinc negative electrode of this embodiment is low, which is 0.0068 mA cm -2 .

[0130] The symmetrical battery of this example also exhibits low polarization potential (-30 to +34 mV) and excellent cycle stability (about 750 h).

[0131] Example 8

[0132] This embodiment provides a porous zinc negative electrode and a preparation method thereof, and a battery. The preparation method of the porous zinc negative electrode includes:

[0133] (1) Cut the zinc plate into 3 cm × 4 cm pieces, wash with ethanol and water to remove organic matter on the surface of the zinc plate, dry it, and then use a press to flatten the cut zinc plate;

[0134] (2) preparing a hydrochloric acid solution with a hydrochloric acid concentration of 2 mol / L, adding the washed and dried zinc plate, and subjecting to ultrasonic reaction for 5 min. After the reaction, the zinc plate was washed with deionized water until it was neutral, and then dried at 60° C.;

[0135] (3) The zinc plate obtained in step (2) was immersed in a mixed solution containing 20 mmol / L sodium stannate, 0.2 mol / L citric acid and hydrochloric acid, and reacted at 40° C. for 5 min. After the reaction, it was washed with deionized water until neutral, and finally dried at 60° C. to obtain a porous zinc negative electrode.

[0136] The corrosion current of the porous zinc negative electrode of this embodiment is shown in Table 1. It can be seen that the corrosion current of the porous zinc negative electrode of this embodiment is low, which is 0.0209 mA cm -2 .

[0137] The symmetrical battery of this example also exhibits low polarization potential (-36 to +40 mV) and excellent cycle stability (about 630 h).

[0138] The inventor has conducted a large number of experimental studies during the research process, and now uses some solutions with poor performance as comparative examples.

[0139] Comparative Example 1

[0140] This comparative example provides a zinc negative electrode and a preparation method thereof, and a battery. The preparation method of the zinc negative electrode includes:

[0141] The zinc plate was cut into 3 cm × 4 cm pieces, washed with ethanol and water to remove organic matter on the surface, and after drying, the cut zinc plate was flattened with a press to obtain a zinc negative electrode.

[0142] Fig.11 The scanning electron microscope image of the zinc negative electrode of Comparative Example 1. The surface of the zinc negative electrode of Comparative Example 1 is uneven and has pits, which will lead to uneven electric field / current distribution on the surface of the zinc negative electrode, thereby promoting the growth of zinc dendrites. Therefore, the symmetrical battery assembled based on the zinc negative electrode of Comparative Example 1 fails within 500h (such as Fig.12 The sample of comparative example 1 has a polarization potential as high as -50 to +60 mV and a high corrosion current (0.0295 mA cm -2 ).

[0143] Comparative Example 2

[0144] This comparative example provides a zinc negative electrode and a preparation method thereof, and the preparation method of the zinc negative electrode comprises:

[0145] (1) Cut the zinc plate into 3 cm × 4 cm pieces, wash it with ethanol and water to remove organic matter on the surface, and press the cut zinc plate flat with a press after drying;

[0146] (2) preparing a hydrochloric acid solution with a concentration of 2 mol / L, adding the washed and dried zinc plate, and subjecting to ultrasonic reaction for 5 min. After the reaction, washing with deionized water until neutral, and drying at 60° C. to obtain a zinc negative electrode.

[0147] Fig.13 The scanning electron microscope image of the zinc negative electrode of Comparative Example 2 is shown in FIG. From the figure, it can be seen that the surface of the zinc plate presents an array structure composed of a large number of nanosheets, and the structure has a high specific surface area. Figure 2 As shown in the figure, it can be found that after acid treatment, the strength of the Zn (002) crystal plane decreases while the strength of the (101) crystal plane increases, which indicates that the acid treatment can remove part of the chemically unstable (002) crystal plane. Compared with Comparative Example 1, the sample of Comparative Example 2 has a larger corrosion current (0.0347 mA cm -2 ), which indicates that simply increasing the specific surface area of ​​the anode will accelerate the corrosion of the Zn anode.

[0148] Comparative Example 3

[0149] This comparative example provides a zinc negative electrode and a preparation method thereof, and the preparation method of the zinc negative electrode comprises:

[0150] (1) Cut the zinc plate into 3 cm × 4 cm pieces, wash it with ethanol and water to remove organic matter on the surface, and press the cut zinc plate flat with a press after drying;

[0151] (2) The zinc plate obtained in step (1) was reacted in a mixed solution containing 20 mmol / L sodium stannate and 0.2 mol / L citric acid at 40° C. for 5 min. After the reaction, it was washed with deionized water until neutral, and finally dried at 60° C. to obtain a zinc negative electrode.

[0152] Fig.14 The scanning electron microscope image of the zinc negative electrode of Comparative Example 3 shows that a large number of Sn nanoparticles are loaded on the surface of the zinc plate, but it does not have a porous structure. The sample of Comparative Example 3 has a lower corrosion current (0.0243 mA cm) than the sample of Comparative Example 1. -2 ), but since Comparative Example 3 does not have a porous structure, its polarization potential is -42 to +46 mV, which is higher than that of Example 1.

[0153] Table 1 Corrosion current of samples in different cases

[0154]

[0155]

[0156] The above description is only a preferred specific implementation manner of the present invention, but the protection scope of the present invention is not limited thereto. Any changes or substitutions that can be easily conceived by any technician familiar with the technical field within the technical scope disclosed by the present invention should be covered within the protection scope of the present invention.

Claims

1. A method for preparing a porous zinc negative electrode, characterized in that: include: Step 1, etching the zinc plate in acid A; Step 2: placing the etched zinc plate into a mixed solution containing tin salt and acid B for reaction to obtain a porous zinc negative electrode.

2. The preparation method according to claim 1, characterized in that: In step 1, the acid A is one or more of hydrochloric acid, sulfuric acid, phosphoric acid, oxalic acid, nitric acid, tartaric acid, acetic acid and boric acid.

3. The preparation method according to claim 1, characterized in that: In the step 1, the concentration of acid A is 0.1 to 12 mol / L.

4. The preparation method according to claim 1, characterized in that: In the step 2, the tin salt is a soluble tin salt.

5. The preparation method according to claim 4, characterized in that: The soluble tin salt is one or more of sodium stannate, potassium stannate, tin dichloride, tin tetrachloride and stannous sulfate.

6. The preparation method according to claim 1, characterized in that: In the step 2, the concentration of the tin salt in the mixed solution is 5 to 50 mmol / L.

7. The preparation method according to claim 1, characterized in that: In step 2, the acid B is one or more of citric acid, hydrochloric acid, sulfuric acid and phosphoric acid.

8. The preparation method according to any one of claims 1 to 7, characterized in that: In the step 2, the reaction temperature is 25-60°C.

9. A porous zinc negative electrode, characterized in that: The porous zinc negative electrode is prepared by the preparation method according to any one of claims 1 to 8.

10. A battery, characterized in that: The battery comprises the porous zinc negative electrode prepared by the preparation method according to any one of claims 1 to 8 or the porous zinc negative electrode according to claim 9.